Síntese e caracterização de hidratos de metano - Silva, Vanessa Silva da (2014)
Gas hydrates are solids formed by crystal structures similar to ice, which may form when the water is in contact with low weight molecular gases (such as H2S, CO2, NH3 and/or light hydrocarbons), under certain conditions of temperature and pressure. Several studies show that gas hydrates may be a wide source of natural gas in the future, especially considering the fact that oil production tends to decline due to the high cost involved, which makes the interest in alternative sources, such as natural gas derived from unconventional sources, grow. However, in order to make gas hydrate exploitation possible, it's necessary to know how they are formed and what are the conditions that provide stability and dissociation. Different apparatus have been used to obtain gas hydrate. In this scenario, the present paper aims to use a unique system called Pilot Plant Synthesis of Gas Hydrates to synthesize different hydrates, with different compositions, in various reaction conditions. It is noticed that the present study was based on the synthesis of hydrates with its precipitation of at larger scales. The methane hydrates were characterized by X-ray diffractometer, Gas Chromatograph and Gas Chromatography Isotope Ratio Mass Spectrometer.